1997
DOI: 10.1021/la9702648
|View full text |Cite
|
Sign up to set email alerts
|

Defect Sites on TiO2(110). Detection by O2 Photodesorption

Abstract: The TiO2(110) surface, prepared with different densities of anion vacancy defect sites, has been investigated by studies of O2 photodesorption at 105 K. Two separate O2 photodesorption processes, α1 and α2, are detected and are postulated to be due to the presence of two different types of defect sites produced by annealing the crystal in vacuum before O2 adsorption. The measured photodesorption cross sections for these two states are Q α 1 -O 2 = (3.1 ± 0.2) × 10-16 cm2 and Q α 2 -O 2 = (4.3 ± 0.3) × … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
151
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 124 publications
(169 citation statements)
references
References 44 publications
14
151
0
2
Order By: Relevance
“…[19] Abstract: Samples of the anatase phase of titania were treated under vacuum to create Ti 3 + surface-defect sites and surface O À and O 2 À species (indicated by electron paramagnetic resonance (EPR) spectra), accompanied by the disappearance of bridging surface OH groups and the formation of terminal Ti 3 + À OH groups (indicated by IR spectra). EPR spectra showed that the probe molecule [Re 3 (CO) 12 (CO) 12 H 3 ] is adsorbed on a titania surface with Ti Titania surfaces incorporating Ti 3 + sites can be monitored with techniques such as X-ray photoelectron spectroscopy, [20] ultraviolet photoelectron spectroscopy, [21] and electron paramagnetic resonance (EPR) spectroscopy. [22] Molecular probes have also been used to characterize defect sites on rutile (1 1 0) by thermal desorption (temperature-programmed desorption), with the probe molecules being O 2 , which is photodesorbed, [12] and CO 2 and CO, which are thermally desorbed.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…[19] Abstract: Samples of the anatase phase of titania were treated under vacuum to create Ti 3 + surface-defect sites and surface O À and O 2 À species (indicated by electron paramagnetic resonance (EPR) spectra), accompanied by the disappearance of bridging surface OH groups and the formation of terminal Ti 3 + À OH groups (indicated by IR spectra). EPR spectra showed that the probe molecule [Re 3 (CO) 12 (CO) 12 H 3 ] is adsorbed on a titania surface with Ti Titania surfaces incorporating Ti 3 + sites can be monitored with techniques such as X-ray photoelectron spectroscopy, [20] ultraviolet photoelectron spectroscopy, [21] and electron paramagnetic resonance (EPR) spectroscopy. [22] Molecular probes have also been used to characterize defect sites on rutile (1 1 0) by thermal desorption (temperature-programmed desorption), with the probe molecules being O 2 , which is photodesorbed, [12] and CO 2 and CO, which are thermally desorbed.…”
Section: Introductionmentioning
confidence: 99%
“…EPR spectra showed that the probe molecule [Re 3 (CO) 12 (CO) 12 H 3 ] is adsorbed on a titania surface with Ti Titania surfaces incorporating Ti 3 + sites can be monitored with techniques such as X-ray photoelectron spectroscopy, [20] ultraviolet photoelectron spectroscopy, [21] and electron paramagnetic resonance (EPR) spectroscopy. [22] Molecular probes have also been used to characterize defect sites on rutile (1 1 0) by thermal desorption (temperature-programmed desorption), with the probe molecules being O 2 , which is photodesorbed, [12] and CO 2 and CO, which are thermally desorbed. [13,23] These methods distinguish Ti 3 + from Ti 4 + sites, for example.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations